2002
DOI: 10.1099/00207713-52-1-109
|View full text |Cite
|
Sign up to set email alerts
|

Alicyclobacillus herbarius sp. nov., a novel bacterium containing omega-cycloheptane fatty acids, isolated from herbal tea.

Abstract: A thermo-acidophilic gram-positive bacterium, strain CP-1T, which grows aerobically at 35-65 degrees C (optimum 55-60 degrees C) and at pH 3.5-6.0 (optimum pH 4.5-5.0), was isolated from a herbal tea made from the dried flowers of hibiscus. Phylogenetic analysis of the 16S rRNA gene sequences showed that this bacterium was clearly distinguishable from previously described species of the genera Alicyclobacillus and Sulfobacillus. Strain CP-1T had unique omega-cycloheptane fatty acids as the major membrane lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 21 publications
3
46
0
3
Order By: Relevance
“…The family Alicyclobacillaceae of the order Bacillales includes mesophilic, acidophiles and moderately (or slightly) thermophilic acidophiles (Dufresne et al, 1996;Goto et al, 2002aGoto et al, , b, 2003Matsubara et al, 2002;Tsuruoka et al, 2003). When two Sulfobacillus species were cultivated at optimum growth temperature, spermine level was higher at higher temperatures.…”
Section: Bacillalesmentioning
confidence: 99%
See 1 more Smart Citation
“…The family Alicyclobacillaceae of the order Bacillales includes mesophilic, acidophiles and moderately (or slightly) thermophilic acidophiles (Dufresne et al, 1996;Goto et al, 2002aGoto et al, , b, 2003Matsubara et al, 2002;Tsuruoka et al, 2003). When two Sulfobacillus species were cultivated at optimum growth temperature, spermine level was higher at higher temperatures.…”
Section: Bacillalesmentioning
confidence: 99%
“…The thermophilic anaerobes, Gelria (Plugge et al, 2002), Thermanaerovibrio (Baena et al, 1999b), Thermosyntropha (Svetlitshnyi et al, 1996), Thermicanus (Gossner et al, 1999) and Thermobrachium (Engle et al, 1996), and the mesophiles, Aminobacterium and Aminomonas (Baena et al, 1999a(Baena et al, , 2000, and several anaerobes located in the Desulfotomaculum lineage I (Brauman et al, 1998;Fardeau et al, 1995;Imachi et al, 2002;Qiu et al, 2003;Robertson et al, 2001), and the alkaliphilic clostridia, Alkaliphilus (Cao et al, 2003;Takai et al, 2001b) were available in the present study. Polyamines of thermophilic Anoxybacillus and Ureibacillus (Belduz et al, 2003;Fortina et al, 2001;Yumoto et al, 2004), as well as thermoacidophilic Sulfobacillus and Alicyclobacillus (Dufresne et al, 1996;Goto et al, 2002aGoto et al, , b, 2003Matsubara et al, 2002;Tsuruoka et al, 2003), were also determined.…”
mentioning
confidence: 99%
“…5B) and could probably compete well with other organisms, since T1 became a dominant PLFA after prolonged incubations at 55°C. The identification of T1 as an -cycloheptyl and T2 and T3 as -cyclohexyl fatty acids indicated that the microorganisms were members of the genus Alicyclobacillus, which is characterized by large amounts of these rare fatty acids (4,10,19). Among Bacillus-related genera, Alicyclobacillus is characterized as thermophilic, aerobic, heterotrophic, and preferring acid conditions (4,5), which fits with the environmental conditions in heated peat.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Alicyclobacillus hesperidum (Albuquerque et al, 2000), ' Alicyclobacillus mali ' and ' Alicyclobacillus acidocaldarius subsp. rittmannii ' (Nicolaus et al, 1998), which possess ω-cyclohexane fatty acid, and Alicyclobacillus herbarius (Goto et al, 2002), which possesses ω-cycloheptane fatty acid, have been reported. In the preceding studies, strains of the genus Alicyclobacillus had been isolated from geothermal sources, and, subsequently, also from non-geothermal soils.…”
mentioning
confidence: 99%